Incentivizing Primary Care Providers to Innovate: Building Medical Homes in the Post‐Katrina New Orleans Safety Net. (26th June 2013) - Rittenhouse, Diane R.; Schmidt, Laura A.; Wu, Kevin J.; Wiley, James
<x xml:space="preserve">Abstract</x> Objective To evaluate safety‐net clinics' responses to a novel community‐wide Patient‐Centered Medical Home (PCMH) financial incentive program in post‐Katrina New Orleans. Data Sources/Study Setting Between June 2008 and June 2010, we studied 50 primary care clinics in New Orleans receiving federal funds to expand services and improve care delivery. Study Design Multiwave, longitudinal, observational study of a local safety‐net primary care system. Data Collection Clinic‐level data from a semiannual survey of clinic leaders (89.3 percent response rate), augmented by administrative records. Principal Findings Overall, 62 percent of the clinics responded to financial incentives by achieving PCMH recognition from the National Committee on Quality Assurance (NCQA). Higher patient volume, higher baseline PCMH scores, and type of ownership were significant predictors of achieving NCQA recognition. The steepest increase in adoption of PCMH processes occurred among clinics achieving the highest, Level 3, NCQA recognition. Following NCQA recognition, 88.9 percent stabilized or increased their use of PCMH processes, although several specific PCMH processes had very low rates of adoption overall. Conclusions Findings demonstrate that widespread PCMH implementation is possible in a safety‐net environment when external financial incentives are aligned with the goal of practice innovation.